Impact of transitioning patients to oral diuretics 24 hours before discharge from heart failure hospitalization on 30 day outcomes. (1st October 2022) - Epstein, Elizabeth; Schale, Stephen; Brambatti, Michela; You, Hyeri; Hansen, Paul; McCain, Julia; Lin, Jessica; Greenberg, Barry
Abstract: Background: Patients hospitalized for heart failure (HF) are at high risk for post-discharge events. Although transition from intravenous to oral diuretics for ≥24 h is commonly practiced to reduce post-discharge risk, evidence supporting this strategy is limited. We investigated the impact of this practice on 30 day post-discharge outcomes following HF hospitalization at our institution. Methods: Retrospective chart review of patients hospitalized with a primary HF diagnosis, discharged on oral diuretic, and followed at our institution. Admission, in-hospital, and pre-discharge characteristics of patients discharged with ≥24-h observation were compared to those of patients observed for <24-h on oral diuretics. Differences between groups in composite 30 day all-cause mortality and rehospitalization, each component, and HF rehospitalization were assessed. Results: Of 285 patients meeting entry criteria, 178 received oral diuretics ≥24 h prior to discharge and 107 were discharged <24 h after transitioning to oral diuretics. Baseline characteristics were similar between groups. Patients with ≥24 h observation on oral diuretics had longer in-hospital stays and greater weight and net volume loss than those observed <24 h. Patients receiving oral diuretics for <24 h were more likely to have had neurohormonal drugs and diuretic dose changed within 24-h of discharge. Oral diuretic treatment for ≥24 h failed to reduce any study endpoint. Conclusions: Transitioning patients to oral diuretics for ≥24 h prior to discharge following HF hospitalization failed to improve 30-day outcomes. These results question this strategy for all patients hospitalized for worsening HF. Highlights: Transitioning patients to oral diuretics for ≥24 h prior to discharge is common. Evidence that this strategy improves outcomes is limited. This study investigated the impact of this practice on post-discharge outcomes. Treatment with oral diuretics for ≥24 h did not improve 30 day outcomes.